On Indian ground : northern Plains - Gipp, Gerald E.; Fox, Sandra; Comeau,Karen Gayton (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"On Indian Ground: Northern Plains is the fourth of ten regionally focused texts that explores American Indian/Alaska Native/Native Hawaiian education in depth. The text is designed to be used by educators of native youth and emphasizes best practices found throughout the state. Previous texts on American Indian education make wide-ranging general assumptions that all American Indians are alike. This series promotes specific interventions and relies on native ways of knowing to highlight place-based educational practices. On Indian Ground, Northern Plains looks at the history of Indian education with the states North Dakota, South Dakota, Wyoming, Montana, Idaho, and Nebraska. Authors also analyze education policy and tribal education departments to highlight early childhood education, gifted and talented educational practice, parental involvement, language revitalization, counseling, and research. These chapters expose cross-cutting themes of sustainability, historical bias, economic development, health and wellness and cultural competence. The intended audience for this publication is primarily those educators who have American Indian/Alaska Native/Native Hawaiian in their schools. The articles range from early childhood and head start practices to higher education, including urban, rural and reservation schooling practices"-- Provided by publisher.
Keywords: Indians of North America -- Education -- Northwestern States.; Education -- Multicultural Education.; Educational strategies and policy: inclusion.; Educational strategies and policy.; Ethnic groups and multicultural studies.; elektronické knihy; electronic books